Early Onset of Tenofovir-Related Fanconi Syndrome in a Child with Acute Hepatitis B: A Case Report and Systematic Review of Literature - Renato Pascale; Viola Guardigni; Lorenzo Badia; Francesca Volpato; Pierluigi Viale; Gabriella Verucchi (Case Reports in Hepatology)
Tenofovir disoproxil fumarate- (TDF-) related nephropathy is known to be a long-term complication of this drug, more commonly observed in HIV-infected patients, but occurring also in hepatitis B. Cases of Fanconi Syndrome associated with TDF have been reported in adult patients, usually as a long-term complication of chronic hepatitis B treatment. We present here a case of a 12-year-old male developing a severe acute HBV hepatitis treated with TDF. The patient achieved an early virological and biochemical response, but with a subsequent onset of proximal renal tubular damage, consistent with Fanconi Syndrome. After withdrawing this drug and switching to Entecavir, a complete resolution of tubulopathy and, after 6 months, a complete HBsAg seroconversion occurred. To our knowledge, this is the first report of an early renal injury due to TDF-therapy in a pediatric patient treated for acute hepatitis B.